Ontological Balance in Educational Management and Its Impact on Educational Service Quality - Heni Suhertini; Irawan; Rohmat Mulyana Sapdi (Al-Qalam Institue, 2026)
This study aims to examine how educational managers’ ontological balance influences the quality of educational services, with a specific focus on the integration of professional responsibilities and spiritual values in madrasah governance. A mixed-methods case study design was employed, combining quantitative surveys of managers, teachers, and students with in-depth interviews and document analysis. Quantitative data were analyzed using descriptive statistics, while qualitative data were processed through thematic analysis. The findings show that the level of ontological balance among educational managers is high, although variations appear across spiritual, value-oriented, and professional dimensions. Educational service quality is generally rated good, yet inconsistencies remain in implementation practices and feedback mechanisms. The analysis indicates a significant positive relationship between ontological balance and service quality, particularly in exemplary behavior, policy integrity, and communication practices. The study implies that strengthening managers’ ontological balance through value-based leadership development, structured professional reflection, and continuous capacity-building can meaningfully enhance madrasah service quality.